2016
DOI: 10.1038/srep25551
|View full text |Cite
|
Sign up to set email alerts
|

The accommodative ciliary muscle function is preserved in older humans

Abstract: Presbyopia, the loss of the eye’s accommodation capability, affects all humans aged above 45–50 years old. The two main reasons for this to happen are a hardening of the crystalline lens and a reduction of the ciliary muscle functionality with age. While there seems to be at least some partial accommodating functionality of the ciliary muscle at early presbyopic ages, it is not yet clear whether the muscle is still active at more advanced ages. Previous techniques used to visualize the accommodation mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Restoring function similar to the biological solution for the young eye is still the 'holy grail' of presbyopia correction. As mentioned, the ciliary muscle retains some contractility even in an aged eye, giving hope that implanting a suitably flexible IOL into the excavated lens capsule following cataract surgery could restore accommodation (Tabernero et al, 2016). However, the surgery itself alters the anatomy of the anterior chamber, resulting in a decrease in lens thickness, which has been shown to increase ciliary body movement and altered the ciliary body shape through iris posterior displacement (Fayed, 2017), which needs to be taken into account.…”
Section: 'Accommodating' Iolsmentioning
confidence: 99%
“…Restoring function similar to the biological solution for the young eye is still the 'holy grail' of presbyopia correction. As mentioned, the ciliary muscle retains some contractility even in an aged eye, giving hope that implanting a suitably flexible IOL into the excavated lens capsule following cataract surgery could restore accommodation (Tabernero et al, 2016). However, the surgery itself alters the anatomy of the anterior chamber, resulting in a decrease in lens thickness, which has been shown to increase ciliary body movement and altered the ciliary body shape through iris posterior displacement (Fayed, 2017), which needs to be taken into account.…”
Section: 'Accommodating' Iolsmentioning
confidence: 99%
“…In this study, we performed the additional analysis of the axial rotation for each IOL models. In a real pseudophakic eye, this kind of movement can be associated with the residual activity of the accommodation mechanism, which was proved 38 to be preserved after IOL implantation. Figure 8(a) shows these results as a function of the clamp displacement.…”
Section: Defocusmentioning
confidence: 99%
“…Although the ciliary muscle is probably the most difficult structure to visualize, the UBM and OCT systems have enabled the study of this structure. In particular, studies have assessed differences in the diameter of the ciliary muscle in phakic and pseudophakic eyes (7) , morphologic changes in the ciliary body with accommodation in children and young adults (8)(9)(10)(11)(12) , and the effect of phenylephrine on the ciliary muscle (13) . These studies have reported differences in ciliary muscle morphology between young and adult eyes, although these differences have not been shown to affect the ability of the ciliary muscle to accommodate (12) .…”
Section: Multisectorial Changes In the Ciliary Muscle During Accommodmentioning
confidence: 99%
“…In particular, studies have assessed differences in the diameter of the ciliary muscle in phakic and pseudophakic eyes (7) , morphologic changes in the ciliary body with accommodation in children and young adults (8)(9)(10)(11)(12) , and the effect of phenylephrine on the ciliary muscle (13) . These studies have reported differences in ciliary muscle morphology between young and adult eyes, although these differences have not been shown to affect the ability of the ciliary muscle to accommodate (12) . In addition to these results, it should be borne in mind that most studies assessed changes in the nasal and temporal ciliary muscle (8,9,14,15) or only in the nasal (16) or temporal sections (10,11,13) .…”
Section: Multisectorial Changes In the Ciliary Muscle During Accommodmentioning
confidence: 99%